TINJAUAN YURIDIS TERHADAP WEWENANG BUPATI/ WALIKOTA DALAM MELAKUKAN KLARIFIKASI PERATURAN DESA - Kartika Sari, Ni Putu Riyani; Dianthi, Ni Made Mutia Risna; Prayoga, I Wayan Didik (Fakultas Hukum Universitas Ngurah Rai, 2023)
Village regulations are defined as statutory regulations which regulated by the Village Headafter being discussed and agreed with the Village Consultative Body. It’s position in the systemof laws and regulations in Indonesia gains legitimacy in Article 8 of Law 12/2011. The authorityof the Regent/Mayor to clarify village regulations is part of the village guidance and supervisionauthority granted by the Village Law. Theoretically, this authority is a form of executive review inrealizing the synchronization of laws and regulation